The Genesis and Development of Children’s Libraries in the Independent Republic of Latvia (1918−1940) - Dreimane, Jana (Knygotyra, 2021)
The article is dedicated to one of the “blank pages” in the historiography of Latvian libraries − the beginnings of children’s departments in public libraries and independent children’s libraries, from the idea, its implementation and the first twenty years of operation in the independent Republic of Latvia (1918−1940). As there are no academic or popular publications on this topic, the so-called historical method is used in the research, which allows the reconstruction of the emergence and development of Children’s departments in public libraries and children’s libraries in the context of the library sector’s development in Europe and the United States. The main base of the research: press articles and books of the respective period, as well as documents in the National Archives of Latvia on the children’s departments of Rīga public libraries. The study shows that the ideological justification for free children’s libraries in Latvia was the same as in Russia and Sweden: the public’s desire to protect children and young people from the harmful effects of “pulp” literature (at that time even the term “dirty” literature was used) and to offer them “good” books instead. However, at the beginning of the 20th century, Latvia lacked the main precondition – a network of free public libraries, within which children’s departments in public libraries or independent children’s libraries could be organised. The first children’s department in a public library was only opened in December 1919 in Liepāja (the largest city in Latvia’s Kurzeme region), thanks to the enthusiasm of publicist and politician, library manager Voldemārs Caune and his conviction of the need for such a service. Until the Soviet occupation, it was the only children’s department at a public library in the province. The situation in the capital Rīga was different. Here, the first children’s department aimed at reducing the “book famine” was established by the State Library of Latvia in February 1922, but soon other organisations became involved in the provision of library services to the younger generation. During the first period of independence of the Republic of Latvia, ten Children’s departments were opened in the public library system and at least ten more children’s libraries were opened by charity organisations in different city districts. The encouragement of Caune and like-minded enthusiasts, mostly members of the Latvian Social Democratic Workers’ Party (Hermanis Kaupiņš, Teodors Līventāls, Emma Kalniņa, etc.) also played an important role in their establishment, as did the municipality’s readiness to provide the necessary financial support. Although the Liepāja and Rīga children’s libraries were used very actively, insufficient state and local government funding for libraries hindered the establishment of special library services for children in the rest of Latvia. Thus, until the Soviet occupation in 1940, a network of children’s departments at public libraries and children’s libraries was created only in Rīga. The Soviet occupation saw a new phase in the development of children’s library services, as the establishment of children’s departments at public libraries or separate children’s libraries became mandatory throughout Latvia.